Scheduling against an adversarial network - Leonardi, S.; Marchetti-Spaccamela, A.; Meyer auf der Heide, Friedhelm (SPAA '04: Proceedings of the sixteenth annual ACM symposium on Parallelism in algorithms and architectures)

Global optimization of silicon nanoclusters - Chaudhuri, I.; Sertl, S.; Hajnal, Z.; Dellnitz, M.; Frauenheim, Th. (Applied Surface Science)

New spectral lower bounds on the bisection width of graphs - Bezrukov, S.; Elsässer, R.; Monien, B.; Preis, R.; Tillich, J.-P. (Theoretical Computer Science)

A Rigorous Numerical Method for the Global Analysis of Infinite-Dimensional Discrete Dynamical Systems - Day, S.; Junge, O.; Mischaikow, K. (SIAM Journal on Applied Dynamical Systems)

Optimal Diffusion Schemes and Load Balancing on Product Graphs - Elsässer, Robert; Monien, Burkhard; Preis, Robert; Frommer, Andreas (Parallel Processing Letters)
We discuss nearest neighbor load balancing schemes on processor networks which are represented by a cartesian product of graphs and present a new optimal diffusion scheme for general graphs. In the first part of the paper, we introduce the Alternating-Direction load balancing scheme, which reduces the number of load balance iterations by a factor of 2 for cartesian products of graphs. The resulting flow is theoretically analyzed and can be very high for certain cases. Therefore, we further present the Mixed-Direction scheme which needs the same number of iterations but computes in most cases a much smaller flow. In the second part of the paper, we present a simple optimal diffusion scheme for general graphs, calculating a balancing flow which is minimal in the l 2 norm. It is based on the spectra of the graph representing the network and needs only m-1 iterations to balance the load with m being the number of distinct eigenvalues. Known optimal diffusion schemes have the same performance, however the optimal scheme presented in this paper can be implemented in a very simple manner. The number of iterations of optimal diffusion schemes is independent of the load scenario and, thus, they are practical for networks which represent graphs with known spectra. Finally, our experiments exhibit that the new optimal scheme can successfully be combined with the Alternating-Direction and Mixed-Direction schemes for efficient load balancing on product graphs.

A set oriented approach to global optimal control - Junge, Oliver; Osinga, Hinke M. (ESAIM: Control, Optimisation and Calculus of Variations)

Uncertainty in the dynamics of conservative maps - Junge, O.; Marsden, J.E.; Mezic, I. (2004 43rd IEEE Conference on Decision and Control (CDC) (IEEE Cat. No.04CH37601))

openVisaar: Enriching Cooperative Visualization by Combining Open Technologies - Goetz, Frank; Domik, Gitta (Cooperative Design, Visualization, and Engineering, First International Conference, (CDVE) 2004, Palma de Mallorca, Spain, September 19-22, 2004, Proceedings)

An XML-based visual shading language for vertex and fragment shaders - Goetz, Frank; Borau, Ralf; Domik, Gitta (Proceeding of the Ninth International Conference on 3D Web Technology, Web3D 2004, Monterey, California, USA, April 5-8, 2004)

Operating systems for reconfigurable embedded platforms: online scheduling of real-time tasks - Steiger, Christoph; Walder, Herbert; Platzner, Marco (IEEE Transactions on Computers)

Multipath-Resistant Time of Arrival Estimation for Satellite Positioning - Bischoff, R.; Haeb-Umbach, Reinhold; Nammi, Sai Ramesh (AEUe, Int. Journal on Electronics and Communications)
Satellite positioning systems, such as GPS or the future European system Galileo, employ direct-sequence spread-spectrum signals. The positioning accuracy is strongly affected by the quality of the pseudo range measurements. These measurements necessitate code and carrier synchronization of the received signal with the internally generated reference signals. In this type of systems one major error source is the multipath phenomenon, which results in a sum of delayed and weighted copies of the original signal to be present at the receiver input. This can result in a systematic error of the code tracking loop resulting in range errors in the order of several tens of meters. In this paper we propose an extension of the standard code tracking loop capable of estimating the parameters of the line-of-sight (LOS) signal and separating the LOS from the reflected signal portions. It is based on an analysis of the cross correlation of the received signal with a locally generated code sequence in the vicinity of the tracking point of a Delay-Locked Loop (DLL). For this reason, we call this method Cross Correlation Function (CCF) Analysis. The proposed method achieves considerably more accurate estimates than a DLL. Its performance is comparable to the Multipath Estimating Delay-Locked Loop (MEDLL) which is considered to be the best method for reducing multipath induced errors, so far. However, the computational complexity of the CCF Analysis is by a factor of three smaller compared to the MEDLL. Extensive simulations have been conducted for the proposed method and the MEDLL in order to assess the robustness of the two approaches under various signal constellations.

Soft Features for Improved Distributed Speech Recognition over Wireless Networks - Haeb-Umbach, Reinhold; Ion, Valentin (International Conference on Spoken Language Processing (ICSLP 2004))
A major drawback of distributed versus terminal-based speech recognition is the fact that transmission errors can lead to degraded recognition performance. In this paper we employ soft features to mitigate the effect of bit errors on wireless transmission links: At the receiver a posteriori probabilities of the transmitted feature vectors are computed by combining bit reliability information provided by the channel decoder and a priori knowledge about residual redundancy in the feature vectors. While the first-order moment of the a posteriori probability function is the MMSE estimate, the second-order moment is a measure of the uncertainty in the reconstructed features. We conducted realistic simulations of GSM transmission and achieved significant improvements in word accuracy compared to the error mitigation strategy described in the ETSI standard.

Robust speaker direction estimation with particle filtering - Warsitz, Ernst; Haeb-Umbach, Reinhold (IEEE Workshop on Multimedia Signal Processing (MMSP 2004))
The paper is concerned with binaural signal processing for a bimodal human-robot interface with hearing and vision. The two microphone signals are processed to obtain an enhanced single-channel input signal for the subsequent speech recognizer and to localize the acoustic source, an important information for establishing a natural human-robot communication. We utilize a robust adaptive algorithm for filter-and-sum beamforming (FSB) and extract speaker direction information from the resulting FIR filter coefficients. Further, particle filtering is applied which conducts a nonlinear Bayesian tracking of speaker movement. Good location accuracy can be achieved even in highly reverberant environments. The results obtained outperform the conventional generalized cross correlation (GCC) method.
Keywords: bimodal human-robot interface; binaural signal processing; enhanced single-channel input signal; filter-and-sum beamforming; filtering theory; FIR filter coefficient; generalized cross correlation method; microphones; microphone signal; nonlinear Bayesian tracking; particle filtering; robust adaptive algorithm; robust speaker direction estimation; signal processing; speech enhancement; speech recognition; speech recognizer; user interfaces

Adaptive Beamforming Combined with Particle Filtering for Acoustic Source Localization - Warsitz, Ernst; Haeb-Umbach, Reinhold; Peschke, Sven (International Conference on Spoken Language Processing (ICSLP 2004))
While the main objective of adaptive Filter-and-Sum beamforming is to obtain an enhanced speech signal for subsequent processing like speech recognition, we show how speaker localization information can be derived from the filter coefficients. To increase localization accuracy, speaker tracking is performed by non-linear Bayesian state estimation, which is realized by sequential Monte Carlo methods. Improved acquisition and tracking performance was achieved even in highly reverberant environments, in comparison with both a Kalman Filter and a recently proposed Particle Filter operating on the output of a nonadaptive Delay-and-Sum beamformer.

Berufskollegs als Kompetenzzentren und die damit verbundenen Kooperationsanforderungen zwischen Bildungsgängen - Beutner, Marc; Twardy, M (Mensch. Bildung. Beruf. Herausforderungen an die Berufspädagogik. Dortmunder Beiträge zur Pädagogik)

Neue Methoden der Signalauswertung für Ultraschall-Messsysteme - Gulsch, Michael; Henning, Bernd
In der industriellen Messtechnik werden optische, chemische und akustische Messverfahren zur Ermittlung von Prozessgrößen eingesetzt. Dabei haben die akustischen Messverfahren aufgrund ihrer Robustheit und Wartungsfreundlichkeit ein sehr großes Einsatzgebiet. Impulsbasierte Ultraschallmesssysteme werden unter anderem zur Messung von Durchfluss und Füllstand eingesetzt. Zunehmend werden sie aber auch in der Flüssigkeitsanalytik zur Konzentrationsmessung und Stoffanalyse herangezogen. Dabei führen Gasblasen in den zu untersuchenden flüssigen Medien immer wieder zu Problemen, da bei Anwesenheit von Gasblasen die akustischen Stoffkenngrößen verändert werden. Diese Probleme können ihre Ursache auch in der Signalverarbeitung haben. Dieser Beitrag soll zeigen, welche Methoden zur Signalverarbeitung geeignet sind um dieses Problem zu lösen.

1/f-Frequency Fluctations and Phase Noise in MEMS Resonators - Handel, Peter; Henning, Bernd
The classical forms of noise present in the frequency of MEMS resonators have been recently investigated and described in detail. The present paper extends this investigation to 1/f noise. That is of fundamental nature in microelectromechanical systems (MEMS) resonators, and is given by the universal quantum 1/f effect. In recent years new piezoelectric and compound semiconductor materials have been developed along with advanced manufacturing technologies for MEMS including them. These technologies enable the deposition of thin compound semiconductor, or PZT films and their integration into MEMS devices.

Die akustische Impedanz als Messgröße zur Charakterisierung flüssiger Stoffsysteme - Henning, Bernd (Technisches Messen)

A Space Optimization Method for Time-Reversal Super-Focusing - Rautenberg, Jens; Olszewski, Dirk; Henning, Bernd (Proceedings of the Joint Congress CFA/DAGA 2004)
The appliance of time-reversal acoustics to classical trans-ducer design, medical, technical or audible range applica-tions brings forward new ideas whenever we need both, focusing acoustical energy in time and space. Unfortunately, the spatiotemporal focusing is limited through the amount of applied transducer elements as well as the ergodicity and randomness of the cavity [1]. This paper will show how the simulated annealing technique, a multi-objec¬tive optimiza-tion algorithm [2], is used to increase the nar¬rowness of the refocused spot by breaking up randomness for the benefit of ergodicity in a predetermined cavity.

A systematic approach to the assessment of fuzzy association rules - Dubois, D.; Hüllermeier, Eyke; Prade, H. (In Proceedings of the Workshop on Alternative Techniques for Data Mining and Knowledge Discovery, IEEE International Conference on Data Mining, Brighton, UK)